2014
DOI: 10.1007/s00464-014-3430-0
|View full text |Cite
|
Sign up to set email alerts
|

Rectal carcinoids: a systematic review

Abstract: JournalSurgical endoscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 31 publications
4
61
0
9
Order By: Relevance
“…Endoscopic treatment for rectal NETs is considered a curative treatment for lesions ≤ 10 mm in diameter and without lymphovascular invasion or metastasis. However, metastasis was reportedly detected in 9.7% of cases of ≤ 10 mm rectal NETs[13], and the reported range of rates of distant metastasis in patients with rectal NETs is 2%-8%[10,14,15]. In our study, lymphovascular invasion was found in 1 patient.…”
Section: Discussionmentioning
confidence: 42%
“…Endoscopic treatment for rectal NETs is considered a curative treatment for lesions ≤ 10 mm in diameter and without lymphovascular invasion or metastasis. However, metastasis was reportedly detected in 9.7% of cases of ≤ 10 mm rectal NETs[13], and the reported range of rates of distant metastasis in patients with rectal NETs is 2%-8%[10,14,15]. In our study, lymphovascular invasion was found in 1 patient.…”
Section: Discussionmentioning
confidence: 42%
“…As minimally invasive procedures gather momentum and improve in completeness of excision, cut-off sizes may need to be revised. In the series by Gleeson et al [4], no metastases were seen in lesions ≤9 mm, and local resection was deemed safe in lesions between 10 and 16 mm according to McDermott et al [13] (this was, however, a pooled analysis with data quality scoring low/moderate for all series included). In the series of rectal lesions by Yangong et al [3], no recurrence was seen in 248 cases after transanal resection and endoscopic polypectomy.…”
Section: Therapy (Fig 1)mentioning
confidence: 99%
“…However, the patient must be informed that in the case of unfavourable results of the histopathological examination of the tumour removed via TEM, a radical rectal resection may be necessary. In a series of cases described by Gleeson et al, no metastases were found if the lesion size did not exceed 9 mm [35]. Local resection was considered safe in lesions of 10 to 16 mm in diameter in the study by McDermott et al (however, it was a collective analysis, in which the quality of data was evaluated as low or moderate for all the cases included in the series) [36].…”
Section: Szkolenie Podyplomowe Erineal Amputation Are Recommended (*Ementioning
confidence: 99%